PENGEMBANGAN MEDIA GAME EDUKATIF WATERPEDIA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN DAN TANGGUNG JAWAB SISWA KELAS VI SEKOLAH DASAR - Mujianah; Emawati; Juhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims: to develop and determine the level of validity and practicality of the developed waterpedia educational game media in improving the reading comprehension and responsibility skills of sixth grade elementary school students. This research and development refers to the step developed by the Borg and Gall covering ten steps, that is: information collection, planning, initial product development, initial field test, initial product revision, primary field test, product revision, operational field test, and revision of the final product, and dissemination and implementation. Initial field test subjects are student and teacher of fifth grade at the Trewung State Elementary School. The primary field test subjects are student and teacher of sixth grade at Karanglo 1 State Elementary School. The operational field test subjects are 26 students and teacher of VI-A grade at Karanglo II State Elementary School as a control class and 26 students and teacher of VI-B grade at Karanglo II State Elementary School as an experimental class. Data collection is carried out using a product assessment sheet, a teacher's response questionnaire, student’s response questionnaire, a responsible attitude questionnaire, and pre-test and post-test question. Data analysis uses independent sample t-test and paired sample t-tests at level of 0.05 significance. The result of this research shows that waterpedia educational media games are worthy and effectively in improving reading the reading comprehension and responsibility skills of fifth grade at Karanglo II State Elementary School, Pasuruan. The educational media worthiness of the game can be seen from the assessment of the materials expert and media expert on the "very good" category. Teacher and student responses to the educational media games usage indicate that educational games help in the learning process.